Избранные произведения: в 2-х томах (Дмитрий Холендро) - Холендро Дмитрий Михайлович (1987)
Экземпляры: Пф (1987) / Инвентарный номер: 13751 / Авт.знак: Х 71Т. 1 / ГРНТИ: 17.82.30 / ББК: 84(2Pос=Рус)6